Robust voice activity detection using higher-order statistics in the LPC residual domain. - Nemer, E.
This paper presents a robust algorithm for voice activity detection (VAD) based on newly established properties of the higher order statistics (HOS) of speech. Analytical expressions for the third and fourth-order cumulants of the LPC residual of short-term speech are derived assuming a sinusoidal model. The flat spectral feature of this residual results in distinct characteristics for these cumulants in terms of phase, periodicity and harmonic content and yields closed-form expressions for the skewness and kurtosis. Important properties about these cumulants and their similarity with the autocorrelation function are revealed from this exploratory part. They show that the HOS of speech are sufficiently distinct from those of Gaussian noise and can be used as a basis for speech detection. Their immunity to Gaussian noise makes them particularly useful in algorithms designed for low SNR environments. The proposed VAD algorithm combines HOS metrics with second-order measures, such as SNR and LPC prediction error, to classify speech and noise frames. The variance of the HOS estimators is quantified and used to yield a likelihood measure for noise frames. Moreover, a voicing condition for speech frames is derived based on the relation between the skewness and kurtosis of voiced speech. The performance of the algorithm is compared to the ITU-T G.729B VAD in various noise conditions, and quantified using the probability of correct and false classifications. The results show that the proposed algorithm has an overall better performance than G.729B, with noticeable improvement in Gaussian-like noises, such as street and parking garage, and moderate to low SNR
Keywords: Gaussian noise; ITU-T G.729B VAD; LPC prediction error; LPC residual domain; VAD algorithm; Autocorrelation function; Closed-form expressions; Correct classification probability; False classification probability; Flat spectral feature; Fourth-order cumulants; Harmonic content; Higher-order statistics; Kurtosis; Likelihood measure; Low SNR; Noise frames; Periodicity; Phase; Short-term speech; Sinusoidal model; Skewness; Speech detection; Third-order cumulants; Voice activity detection; Voiced speech